2013
DOI: 10.1016/j.drugalcdep.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric analysis of DSM-IV and DSM-5 alcohol use disorders

Abstract: Background With preparations currently being made for the Diagnostic and Statistical Manual of Mental Disorders-5th Edition (DSM-5), one prominent issue to resolve is whether alcohol use disorders are better represented as discrete categorical entities or as a dimensional construct. The purpose of this study was to investigate the latent structure of DSM-Fourth Edition (DSM-IV) and proposed DSM-5 alcohol use disorders. Methods The study used the Wave 2 National Epidemiologic Survey on Alcohol and Related Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
(79 reference statements)
2
16
0
2
Order By: Relevance
“…A summary score of criteria was used (from 0 to 11) instead of the cut-offs described in the DSM-5. Previous studies reported that a continuous dimension better fitted AUD than a categorical one (Kerridge et al, 2013).…”
Section: Methodsmentioning
confidence: 86%
“…A summary score of criteria was used (from 0 to 11) instead of the cut-offs described in the DSM-5. Previous studies reported that a continuous dimension better fitted AUD than a categorical one (Kerridge et al, 2013).…”
Section: Methodsmentioning
confidence: 86%
“…For the previous 12 months, alcohol dependence was assessed with the seven criteria of alcohol dependence from the Diagnostic and Statistical Manual of Mental Disorders (DSM IV) as in Knight et al (2002). We used a continuous numbered scale of the seven criteria (from 0 to 7), instead of a cut-off, because current literature assumes a more continuous dimensional construct to alcohol dependence rather than a categorical model (Knight et al 2002;Kerridge et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…We used a continuous numbered scale of criteria (from 0 "no symptom of dependence" to 7 "high number of symptoms of dependence") instead of a cut-off of 3 or more criteria. This was because current literature assumes a more continuous dimensional construct to alcohol dependence rather than a categorical model [25], and because alcohol dependence may not yet have been diagnosed in such young populations. The level of alcohol use was measured by drinking volume (usual quantity multiplied by frequency of alcohol use) and frequency of risky single-occasion drinking (RSOD, i.e.…”
Section: Alcohol Usementioning
confidence: 99%